The Concept of Sovereignty in a Democratic System According to Murtadha Muthahhari - Gunawan, Deni (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2025)
This article examines the concept of sovereignty in a democratic system according to Murtadha Muthahhari, a prominent contemporary Muslim thinker who significantly contributed to modern Islamic political discourse. The study is motivated by the long-standing debate on the relationship between religion and state, which remains relevant today, particularly in Muslim-majority countries such as Indonesia and Iran. The main objective is to explore Muthahhari’s views on divine and popular sovereignty, as well as his formulation of a religious democracy distinct from Western secular democracy. This research employs a qualitative method with a library research approach and critical analysis of Muthahhari’s primary works, supported by relevant secondary literature. The findings reveal that Muthahhari rejected both the strict separation of religion and state and the idea of a pure theocracy. Instead, he proposed the model of “religious democracy,” which combines divine sovereignty with popular participation within the framework of Shi’a political thought through the concept of Wilāyah al-Faqīh. In this perspective, sovereignty ultimately belongs to God, yet the people retain a significant role in shaping governance. In conclusion, Muthahhari’s political thought provides an alternative perspective in contemporary Islamic political debates while also serving as a critique of Western democratic systems that are often considered secular and individualistic.